Study of the consensus method for a multi-agent system with actuator saturation - Xu, Maolin (Nanyang Technological University, 2024)
The multi-agent system is a group composed of multiple intelligent moving bodies through information interaction. Because of its strong fault tolerance and robustness, it proves instrumental in numerous fields, among which are the military, transportation, production, and several others. Among them, the research on the consistency of multi-agent systems is one of the hot research hotspots within the domain of control systems. With respect to the implementation of engineering solutions, it is very common for multi-agents to receive the constraints of actuator saturation, which significantly affects the coherence of multi-agent networks. So, this article first considers the global consistency problem of the single integrator agent system in the case of actuator saturation. Through the research on the algorithm proposed by the predecessors, we selected a control algorithm with better control performance indicators to solve the global consistency problem of the single integrator agent system with actuator saturation, and it facilitated faster convergence for the distributed agent system. Finally, we also simulated and verified the proposed algorithm. Then this dissertation discusses the optimal consensus problem of multi-agent systems. In order to improve the transmission efficiency between agents and control the communication cost, we introduce an event trigger strategy, the core of which is the event trigger condition, and the triggering condition is dependent on status updates exchanged between agents, and each agent calculates the interpolation between its own state information and that of its neighbors. The system will revise its control status whenever the triggering condition is satisfied. However, in cases where the trigger condition is not satisfied, it will elect not to modify the existing state. The pursuit of optimal consistency leads to a focus on stabilizing the closed- loop system, which is allowed to be validated through the Lyapunov stability theorem. After that, an analytical exploration is conducted regarding Zeno effects resulting from the introduction of triggering events, and then the effectiveness of the proposed control algorithm is verified again through MATLAB simulation experiments.